2015
DOI: 10.1161/cir.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Part 3: Adult Basic Life Support and Automated External Defibrillation

Abstract: Introduction This Part of the 2015 International Consensus on Cardiopul monary Resuscitation (CPR) and Emergency Cardiovascular Care (ECC) Science With Treatment Recommendations (CoSTR) presents the consensus on science and treatment recommendations for adult basic life support (BLS) and automated external defibrillation (AED). After the publication of the 2010 CoSTR, the Adult BLS Task Force developed review questions in PICO (population, intervention, comparator, outcome) format.1 This resulted in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 234 publications
(102 citation statements)
references
References 187 publications
(505 reference statements)
2
95
0
1
Order By: Relevance
“…Following a cardiac arrest, early bystander cardiopulmonary resuscitation (CPR) and defibrillation are both vital components in the chain of survival 1, 2. However, the proportion of patients who receive bystander CPR, following an out‐of‐hospital cardiac arrest (OHCA), is still relatively low in most countries 3.…”
Section: Introductionmentioning
confidence: 99%
“…Following a cardiac arrest, early bystander cardiopulmonary resuscitation (CPR) and defibrillation are both vital components in the chain of survival 1, 2. However, the proportion of patients who receive bystander CPR, following an out‐of‐hospital cardiac arrest (OHCA), is still relatively low in most countries 3.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the prompt/feedback functions on CPR quality are also limited. One of the randomized studies and other observational studies have shown that the prompt/feedback function can reduce the variability of compression rates, but has little or no effect on other aspects of CPR quality, such as compression depth and compression fraction 5, 50, 52. It is also of importance to note that the AED users in these studies were trained personnel.…”
Section: Issues Concerning Pad That Needs To Be Addressedmentioning
confidence: 99%
“…Based on intervention and observational studies, current guidelines strongly recommend the introduction of community‐based PAD programs, with training for nonhealth professionals 5, 18. A cluster randomized controlled study showed that PAD deployment and training of lay volunteers in CPR and AED use significantly increased survival to discharge rates in comparison with volunteer CPR training only (23.4% vs 14.0%; relative risk=2.0) (Table 2).…”
Section: Pad Programsmentioning
confidence: 99%
See 2 more Smart Citations